Fixed-Income Portfolio Analytics (A Practical Guide to Implementing, Monitoring and Understanding Fixed-Income Portfolios) - Bolder, David Jamieson (Springer, 2015)
Global fixed-income markets are enormous and growing. Trillions of dollars in numerous currencies are invested in these markets by a broad range of investors including pension funds, insurance companies, commercial banks, corporate trea suries, endowments, sovereign-wealth funds, and central-bank reserve managers. Each of these investors allocates significant resources towards evaluating, monitor ing, and understanding the day-to-day exposures, performance, and risks associated with the underlying market risk factors found in their portfolios. It is precisely this type of careful attention by individual investors that leads to liquid, well functioning, and efficient markets...